Beanstalker and other hilarious scarytales - White, Kiersten (Scholastic Press, 2017)
Snow White is a vampire, Little Red Riding Hood is a zombie, and Cinderella is an arsonist--and that is only some of the mayhem the reader will find in this collection of fractured fairy tales.